Awakening: exploring spirituality, emergent creativity, and reconciliation - Redekop, Vern Neufeld; Redekop, Gloria Neufeld (Lexington Books, 2025)
Even if all of the elements we know to be significant in the process of reconciliation were present, reconciliation would not necessarily take place. Reconciliation is a nonlinear, nonalgorithmic process that involves "matters of the heart." From emergent creativity and its links to mysticism, to the evolution of emotions as drivers of thought, Awakening weaves cutting-edge discoveries in complexity theory with philosophical reflections on consciousness and language, drawing on Lonergan and Wittgenstein. Awakening as a phenomenon takes on a vibrant vitality as an aspect of transpersonal psychology and it manifests as imperatives to take responsibility for our relationships, to address complex challenges of justice, and to adopt a heart-based approach to peacebuilding